2012
DOI: 10.1063/1.3693393
|View full text |Cite
|
Sign up to set email alerts
|

Green luminescence in silica glass: A possible indicator of subsurface fracture

Abstract: International audienceWe investigate the nature of defects triggering laser damage in fused silica in subsurface fracturesin nanosecond near ultraviolet regime. Mechanical, laser induced surface flaws as well as pristinesilica surface were characterized by optical microscopy and luminescence confocal microscopybefore and after acid etching. In all cases, photoluminescence decreases with etching timeassessing the existence of defects close to the surface. Spectral analysis of the evolution of thesesignals durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…An unexplained green photoluminescence was also evidenced 17 , 18 and potentially involved in the damage initiation process. However, these photo luminescent defects were removed by an HF-based etch of 1 to 2 µm 11 , 19 . The impact of scratch morphology on the electric field distribution and its modification after etching is therefore likely to be responsible for this increase in the threshold.…”
Section: Introductionmentioning
confidence: 99%
“…An unexplained green photoluminescence was also evidenced 17 , 18 and potentially involved in the damage initiation process. However, these photo luminescent defects were removed by an HF-based etch of 1 to 2 µm 11 , 19 . The impact of scratch morphology on the electric field distribution and its modification after etching is therefore likely to be responsible for this increase in the threshold.…”
Section: Introductionmentioning
confidence: 99%
“…According to L. Skuja et al . 18 , 20 , 22 , the lifetimes of these fluorescence defects discussed above are 4 ns (α-ODC(II)), 110 μs (β-ODC(II)) and 300 ns ( E δ ’), respectively. In our case (laser pulse is 6.4 ns), α-ODC(II) might be the main laser damage precursor.…”
Section: Results and Disscusionmentioning
confidence: 95%
“…Figure 3 shows the comparison of normalized fluorescence emission spectra of treated samples. There are three main peaks in the spectra at around 310 nm, 390 nm and 590 nm bands, corresponding to oxygen-deficiency centers (II) (ODC(II), around 290 nm for α band and 390 nm for β band), and E δ ’ center defects (590 nm band), respectively 18 20 . The characterized peak at around 310 nm band is an incomplete peak of ODCs (around 290 nm band) due to the application of filter (290 nm).…”
Section: Results and Disscusionmentioning
confidence: 99%
“…They are buried in the pits, scratches and other mechanical damage in subsurface layer. In addition, studies have shown that this kind of SSDs with fluorescence characteristics is closely related to the laser damage of optics [18,19] .…”
Section: Introductionmentioning
confidence: 97%